Ethics, equity, and regulation - Tinker, Tony; Merino, Barbara Dubis; Neimark, Marilyn Kleinberg (Emerald, 2010)
The aims of Advances in Public Interest Accounting are twofold. Firstly, to provide a forum for researchers concerned with critically appraising and significantly transforming conventional accounting theory, practice, teaching and research. And secondly, to increase the social self-awareness of accounting practitioners, educators, and researchers, encouraging them to assume a greater responsibility for the profession's social role. Additional coverage in each volume includes: recognizing and examining the influences of gender and feminist theory, class and race on accounting practice, education, and research; expanding accounting's focus beyond the behavior of individual corporate entities; encompassing the conflicts of interest within the accounting-regulatory process and effected groups; examining accounting's participation in multinational expansion, consolidations, and changing economies undergoing transformations, such as Eastern and Central Europe and the Former Soviet Union, and the European Community.
Description based on print version record.
Keywords: Expenditures, Public.; Public interest.; Accounting -- Moral and ethical aspects.; Equality.; elektronické knihy; electronic books